descompune in factori (x+1)³-(x-2)³
va rog urgent
Răspunsuri la întrebare
Răspuns de
2
(x+1)³= x³ + 2x² + 3x +2
(x - 2)³ = x³ - 6x² + 12 x - 8
(x³ + 2x² + 3x +2) - (x³ - 6x² + 12 x - 8) = 8x² - 9x + 10
(x - 2)³ = x³ - 6x² + 12 x - 8
(x³ + 2x² + 3x +2) - (x³ - 6x² + 12 x - 8) = 8x² - 9x + 10
Alte întrebări interesante
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Franceza,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă